2011
DOI: 10.1080/10810730.2011.604387
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Health Literacy and Older Adults' Assessment of Direct-to-Consumer Prescription Drug Ads

Abstract: Older adults are increasingly the intended target of direct-to-consumer (DTC) prescription drug ads, but limited evidence exists as to how they assess the educational value of DTC ads and, more importantly, whether their assessment depends on their level of health literacy. In-person interviews of 170 older adults revealed that those with low subjective health literacy evaluated the educational value of DTC ads significantly lower than did those with high subjective health literacy. The results prompt us to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Young and Cline () suggest that health literacy is a prerequisite for consumers to comprehend the medical content of ads. Further, An and Muturi () examined the role of subjective health literary in accounting for consumer response to DTCA. The study revealed that those with low subjective health literacy tended to evaluate negatively the effectiveness of DTCA in delivering key medical information, which implies that low ability would be a barrier to consumer processing of risk information even when motivation is reasonably high.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Young and Cline () suggest that health literacy is a prerequisite for consumers to comprehend the medical content of ads. Further, An and Muturi () examined the role of subjective health literary in accounting for consumer response to DTCA. The study revealed that those with low subjective health literacy tended to evaluate negatively the effectiveness of DTCA in delivering key medical information, which implies that low ability would be a barrier to consumer processing of risk information even when motivation is reasonably high.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Nevertheless, even if a lag in the ability to measure exists, there remain other challenges. These include the potential for screening tools and health literacy measurements to cause harm through stigma, embarrassment, or shame of the individual when used in research or clinical care, which may lead to poorer rather than better health outcomes (Paasche-Orlow and Wolf , 2008An and Muturi 2011;Lee, Gazmararian, and Arozullah 2006).…”
Section: Measuring Health Literacymentioning
confidence: 99%
“…The researcher's aim was to examine other factors unrelated to educational levels of older adults which may influence health literacy. It was found that subjective health literacy among individuals was the strongest factor to predict an older adult's assessment of information in DTC ads, when education levels are excluded (An and Muturi 2011).…”
Section: Pilot Studiesmentioning
confidence: 99%
See 2 more Smart Citations